Regulation of net bicarbonate transport in rabbit cortical collecting tubule by peritubular pH, carbon dioxide tension, and bicarbonate concentration. - Breyer, M D (1986)
The effects of changes in peritubular pH, carbon dioxide tension (PCO2), and HCO3- concentration on net HCO3- transport was examined in in vitro perfused cortical collecting tubules (CCTs) from unpretreated New Zealand white rabbits. Lowering peritubular HCO3- concentration and pH by reciprocal replacement of HCO3- with Cl-, significantly stimulated net HCO3- absorption. Lowering peritubular HCO3- concentration and pH, by substitution of HCO3- with gluconate, while keeping Cl- concentration constant, also stimulated net HCO3- absorption. Raising peritubular HCO3- concentration and pH, by reciprocal replacement of Cl- with HCO3-, inhibited net HCO3- absorption (or stimulated net HCO3- secretion). When the tubule was cooled, raising peritubular HCO3- concentration had no effect on net HCO3- transport, suggesting these results are not due to the passive flux of HCO3- down its concentration gradient. The effect of changes in ambient PCO2 on net HCO3- transport were also studied. Increasing the ambient PCO2 from 40 mmHg to either 80 or 120 mmHg, allowing pH to fall, had no effect on net HCO3- transport. Similarly, lowering ambient PCO2 to 14 mmHg had no effect on net HCO3- transport. Simultaneously increasing peritubular HCO3- concentration and PCO2, without accompanying changes in peritubular pH, i.e., isohydric changes, stimulated net HCO3- secretion to the same degree as nonisohydric increases in peritubular HCO3- concentration. Likewise, isohydric lowering of peritubular HCO3- concentration and PCO2 stimulated net HCO3- absorption. We conclude that: acute changes in peritubular HCO3- concentration regulate acidification in the CCT and these effects are mediated by a transcellular process; acute changes in ambient PCO2 within the physiologic range have no effect on HCO3- transport in the in vitro perfused CCT; and acute in vitro regulation of CCT acidification is independent of peritubular pH.